Pendidikan Karakter Berbasis Keagamaan: Studi Kasus di Sekolah Mengaji - Sakinah, Fatiya; Hidayat, Nur (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
The aim of this research is to see how character education in Qur'anic schools can be implemented. Implementation time is taken online. The data collected in this research was obtained through the stages of observation and interviews from Qur'an school teachers in the Temanggung area. The subjects in this research were Koran teachers in the Temanggung area. The results found in this research are the application of Qur’an reading schools in building children's character education. The character education provided is seen from teachers teaching lessons in religious-based Qur'an schools. Suggestions given by the researcher to future researchers are to be able to develop character education in other non-formal education apart from Qur'an reading schools.